2017
DOI: 10.1177/1010428317695930
|View full text |Cite
|
Sign up to set email alerts
|

Expression and associations of TRAF1, BMI-1, ALDH1, and Lin28B in oral squamous cell carcinoma

Abstract: Tumor necrosis factor receptor-associated factor 1, an adaptor protein of tumor necrosis factor 2, is involved in classical nuclear factor (NF)-κB activation and lymphocyte recruitment. However, less is known about the expression and association of tumor necrosis factor receptor-associated factor 1 with cancer stem cell markers in oral squamous cell carcinoma. This study aimed to investigate the expression of tumor necrosis factor receptor-associated factor 1 and stem cell characteristic markers (lin28 homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
2
8
1
3
Order By: Relevance
“…Nevertheless, whether this explanation holds true in patients with OSCC needs to be explored. In the present study, Bmi1 expression did not affect the survival rate of OSCC cases, which was in accordance with other studies by Tamatani et al, 39 Jayasooriya et al, 30 and Wu et al 55 However, Hayry et al 56 found Bmi1 expression to favor better prognosis in tongue carcinoma in contrast to our results. This could be due to the varied pathogenesis involved in OSCC in accordance with different etiological factor and different epithelial types in the population groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, whether this explanation holds true in patients with OSCC needs to be explored. In the present study, Bmi1 expression did not affect the survival rate of OSCC cases, which was in accordance with other studies by Tamatani et al, 39 Jayasooriya et al, 30 and Wu et al 55 However, Hayry et al 56 found Bmi1 expression to favor better prognosis in tongue carcinoma in contrast to our results. This could be due to the varied pathogenesis involved in OSCC in accordance with different etiological factor and different epithelial types in the population groups.…”
Section: Discussionsupporting
confidence: 92%
“…A similar positive association between ALDHI1 and Bmi1 was also observed in oral and oesophageal carcinoma samples. 55 , 64 The HNSCC cell culture studies have noted that ALDH1-positive cells exhibited an increased Bmi1 expression and silencing of Bmi1 greatly reduced the tumorigenicity of the cells and made them more prone to radiotherapy. These results infer a relationship between ALDH and Bmi1.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of TNF receptor-associated factor 1 has been found to be higher in OCSCC than normal oral mucosa and oral epithelial dysplasia, and is associated with reduced overall survival, Moloney murine leukemia virus integration site 1, Lin28 homolog B, and most importantly ALDH1 in OSCC (102). …”
Section: Discussionmentioning
confidence: 99%
“…In human skin, TRAF1 is expressed at higher levels, as measured by histology, in actinic keratosis as well as in squamous cell carcinoma, compared to normal skin (59, 60). Since UV exposure is thought to contribute to these conditions, Yamamoto et al tested the role of UV in induction of TRAF1 in mice.…”
Section: Role Of Traf1 In Cancermentioning
confidence: 99%